Infecciones profundas del cuello - Jiménez Y., Rodrigo; Rappoport W., Daniel; Ramírez, Enrica; Gac E., Patricio; Rodríguez M., Francisco; Cabané T., Patricio (Revista Hospital Clínico Universidad de Chile, 2019)
Deep neck infections (DNIs) are special entities among infectious diseases for their versatility and potential for severe complications. Complex head and neck anatomy often makes early recognition of DNIs challenging, and a high index of suspicion is necessary to avoid any delay in treatment. The diagnosis is made by clinical history, physical examination findings and imaging studies. The treatment consists in securing the airway, intravenous antibiotics and surgical drainage, when needed. To make decisions the surgeon must understand the anatomy of the region, the etiology of infection, appropriate diagnostic tools, and medical and surgical management. This article provides a review of these pertinent topics.